Pengembangan Sistem Informasi Pelayanan Posyandu Tambora Kelurahan Brang Biji Berbasis Android - Desiana Puspita; Shinta Esabella (Buletin Ilmiah Informatika Teknologi, 2022)
Tambora Posyandu is a family Posyandu located in Brang Biji Village, Sumbawa District, Sumbawa Regency, West Nusa Tenggara (NTB). Where the previous Tambora Posyandu Service Information System has conducted research by Rizgika Pusparini, S.Kom with the title Web-Based Posyandu Service Information System Using the Waterfall Method. At the Tambora Posyandu, Brang Biji Village, Sumbawa University of Technology. In this study, the posyandu information system was still offline, so that posyandu members still had difficulty accessing the system. The researcher intends to develop an online web-based posyandu service information system and develop the information system to be android-based. This is taken into account from the posyandu members who are not only from among children, adolescents, and adults but also from the elderly. Where the elderly have difficulty in remembering website addresses. In addition, web-based information systems require a stable internet network. Built with the dart programming language using the flutter framework, and MariaDB databases and system testing that has been carried out using the black-box testing method. It is hoped that the development of an android-based information system can make it easier for posyandu cadres in disseminating information and posyandu members can easily get posyandu information. Development, Information Systems, Services, Posyandu, android, Waterfall, Black Box.